Search 83,581 tutors
FIND TUTORS
Ask a question

Answers by Jean-Guy L.

Ok let us start by changing the equation you gave: 1/x -  3x/2 = x/5 (I just changed the sign of 3x/2) To solve the equation, it is always good to group terms with the same power of x. The 1/x is a power -1 of x or x^-1 while the other terms are a power +1 of x or x^1. By grouping the...

-7y2(-4y3+6y) -> factorize the coefficients we get -7 y2 (- 2.2.y3 + 2.3.y) -> take the 2's in front out of the parenthesis - 7.2 y2 (-2.y3 + 3.y) -> take one y in front out of the parenthesis -14 y3 (-2 y2 + 3) -> take a minus sign -1 in front out of the...

Click this link for a more detailed answer: https://www.dropbox.com/s/v963d9or2g0i9ci/Wyzant%20answers%20%281%29.pdf